The flow experience: Polish adaptation and validation of the psychological flow scale (PFS) - Marcin Wojtasiński; Przemysław Tużnik; Tomasz Jankowski; Silvia Leoni; Mateusz Chwaszcz; Dorota Miszczyszyn; Maria Banasik; Paweł Augustynowicz (PLoS ONE, 2025)
Flow is an absorbing, effortless, and intrinsically rewarding state that unfolds over time. We adapted the nine-item Psychological Flow Scale (PFS) to Polish and evaluated it in a preregistered laboratory study designed to capture fine-grained changes in flow. After individual skill calibration, participants completed a 20-trial pursuit-tracking task following a chaotic Lorenz trajectory; data from 140 participants met inclusion criteria. Multilevel confirmatory factor analysis supported the theorized structure: Absorption, Effortless Control, and Intrinsic Reward formed correlated first-order factors nested under a second-order Flow factor at both the within-person and between-person levels (χ²(46) = 345.35, CFI = 0.98, RMSEA = 0.05). Reliability was excellent for aggregated scores (generalizability RkF = 1.00) and remained high for detecting trial-to-trial change (Rc = 0.88), indicating sensitivity to momentary fluctuations. Convergent validity was evidenced by moderate correlations with the Flow Short Scale administered concurrently (r = .28–.39), low-to-modest correlations with task performance score (r = .13–.32), and low-to-modest associations with the General Flow Proneness Scale (r = .13–.26). Complementary hierarchical exploratory graph analysis corroborated this three-facet-plus-general structure. Collectively, these findings establish the Polish PFS as a reliable, culturally appropriate instrument for tracking the temporal dynamics of optimal experience and illustrate how repeated measurement coupled with multilevel modelling can advance research on flow.